Brain metastases: A Society for Neuro-Oncology (SNO) consensus review on current management and future directions. Issue 10 (28th June 2022) - Aizer, Ayal A; Lamba, Nayan; Ahluwalia, Manmeet S; Aldape, Kenneth; Boire, Adrienne; Brastianos, Priscilla K; Brown, Paul D; Camidge, D Ross; Chiang, Veronica L; Davies, Michael A; Hu, Leland S; Huang, Raymond Y; et al.
Abstract: Brain metastases occur commonly in patients with advanced solid malignancies. Yet, less is known about brain metastases than cancer-related entities of similar incidence. Advances in oncologic care have heightened the importance of intracranial management. Here, in this consensus review supported by the Society for Neuro-Oncology (SNO), we review the landscape of brain metastases with particular attention to management approaches and ongoing efforts with potential to shape future paradigms of care. Each coauthor carried an area of expertise within the field of brain metastases and initially composed, edited, or reviewed their specific subsection of interest. After each subsection was accordingly written, multiple drafts of the manuscript were circulated to the entire list of authors for group discussion and feedback. The hope is that the these consensus guidelines will accelerate progress in the understanding and management of patients with brain metastases, and highlight key areas in need of further exploration that will lead to dedicated trials and other research investigations designed to advance the field.